Blood Pressure Variability and Ocular Vestibular-Evoked Myogenic Potentials Are Independently Associated With Orthostatic Hypotension - Kim, Keun-Tae; Lee, Jeong-Heon; Hong, Jun-Pyo; Park, Jin-Woo; Lee, Sun-Uk; Park, Euyhyun; Kim, Byung-Jo; Kim, Ji-Soo (Journal of clinical neurology (Seoul, Korea), 2024)
We delineated the association between otolithic dysfunction and blood pressure (BP) variability. We prospectively recruited 145 consecutive patients (age=71 [59-79] years, median [interquartile range]; 76 females) with orthostatic intolerance between December 2021 and December 2023 at a tertiary hospital in South Korea. Each patient underwent evaluations of cervical and ocular vestibular-evoked myogenic potentials (oVEMPs), 24-h noninvasive ambulatory BP monitoring (ABPM), and a head-up tilt-table test using the Finometer device. As measures of BP variability, the standard deviations (SDs) of the systolic BP (SBP ) and the diastolic BP were calculated based on serial ABPM recordings. Patients were divided into those with orthostatic hypotension (OH, =68) and those with a normal head-up tilt-table test despite orthostatic intolerance (NOI, =77) groups. A multivariable logistic regression analysis showed that OH was associated with bilateral oVEMP abnormalities ( =0.021), SBP ( =0.012), and female sex ( =0.004). SBP was higher in patients with OH than in those with NOI ( <0.001), and was not correlated with n1-p1 amplitude ( =0.491) or normalized p13-n23 amplitude ( =0.193) in patients with OH. The sensitivity and specificity for differentiating OH from NOI were 72.1% and 67.5%, respectively, at a cutoff value of 12.7 mm Hg for SBP , with an area under the receiver operating characteristic curve of 0.73. Bilaterally deficient oVEMP responses may be associated with OH regardless of 24-h BP variability, reflecting the integrity of the otolith-autonomic reflex during orthostasis. Alternatively, 24-h BP variability is predominantly regulated by the baroreflex, which also participates in securing orthostatic tolerance complementary to the vestibulo-autonomic reflex.